Longitudinal changes in movement-related functional MRI activity in Parkinson's disease patients. (June 2021) - Hannaway, Naomi; Lao-Kaim, Nicholas P.; Martín-Bastida, Antonio; Roussakis, Andreas-Antonios; Howard, Jonathan; Wall, Matthew B.; Loane, Clare; Barker, Roger A.; Piccini, Paola
Abstract: Introduction: Functional brain imaging has shown alterations in the basal ganglia, cortex and cerebellum in Parkinson's disease patients. However, few functional imaging studies have tested how these changes evolve over time. Our study aimed to test the longitudinal progression of movement-related functional activity in Parkinson's disease patients. Methods: At baseline, 48 Parkinson's disease patients and 16 healthy controls underwent structural and functional magnetic resonance imaging during a joystick motor task. Patients had repeated imaging after 18-months (n = 42) and 36-months (n = 32). T-tests compared functional responses between Parkinson's disease patients and controls, and linear mixed effects models examined longitudinal differences within Parkinson's disease. Correlations of motor-activity with bradykinesia, rigidity and tremor were undertaken. All contrasts used whole-brain analyses, thresholded at Z > 3.1 with a cluster-wise P < 0.05. Results: Baseline activation was significantly greater in patients than controls across contralateral parietal and occipital regions, ipsilateral precentral gyrus and thalamus. Longitudinally, patients showed significant increases in cerebellar activity at successive visits following baseline. Task-related activity also increased in the contralateral motor, parietal and temporal areas at 36 months compared to baseline, however this was reduced when controlling for motor task performance. Conclusion: We have shown that there are changes over time in the blood-activation level dependent response of patients with Parkinson's disease undertaking a simple motor task. These changes are observed primarily in the ipsilateral cerebellum and may be compensatory in nature. Highlights: Functional brain responses to movements changed during Parkinson's disease. Functional brain changes were consistently observed in the ipsilateral cerebellum. Cerebellar changes may represent an attempt to partially restore motor function.